Development of Algorithmic Competence of Students in Studying Mathematics: An Experimental Study of the Effectiveness of the Use of Information and Communication Technologies - Karassyova Lyubov Nikolaevna; Kostangeldinova Alma Akzhanovna; Ibraeva Saltanat Nurgazievna; Babaeva Adelia Doolotbayevna; Keldibekova Aida Oskonovna (Qubahan Academic Journal)
In today's world, education is faced with the challenge of incorporating information and communication technologies (ICT) to enhance the learning experience, particularly in mathematics. This research aims to determine the effect of ICT on the growth of algorithmic competency among students in Kazakhstan. Cultivating this skill set is crucial as it encompasses the capacity to tackle intricate mathematical problems by comprehending and utilizing algorithms, which is essential in a rapidly advancing digital society. The research relies on data analysis from global educational assessment initiatives like PISA (Program for International Student Assessment) and TIMSS (Trends in Mathematics and Science Study). These programs offer comprehensive insights into the present state of mathematical abilities among students in Kazakhstan. The findings highlight the need for substantial enhancements in mathematics education, especially in fostering algorithmic thinking skills. Integrating ICT into the learning process appears to be a powerful tool for attaining these objectives.